Unequal Embodiment: Racial and Ethnic Heterogeneity in the Predictors and Age-Related Health Outcomes Associated with Accelerated Biological Aging - Mariela Villalba Madrid; Francisco Ríos Casas; Mateo P Farina (The Journals of Gerontology, Series A: Biological Sciences and Medical Sciences, 2026)
Abstract Background This study investigates whether life-course socioeconomic exposures are similarly associated with accelerated biological aging across racial and ethnic groups, and whether accelerated biological aging predicts health outcomes equivalently across groups. Methods Data came from the Health and Retirement Study (2016-2022). Accelerated biological age was derived from 22 blood-based biomarkers from the 2016 Venous Blood Study. We used linear regression models with interactions between race/ethnicity and life-course exposures (childhood adversity and adult/midlife socioeconomic status (SES)) to assess group differences in accelerated aging. Linear, multinomial, and logistic regression models with interactions between accelerated biological age and race/ethnicity were used to assess group differences in health outcomes. We examined differences by foreign-born status among Hispanic adults. Results Associations between life-course exposures, accelerated biological aging, and health varied by race/ethnicity. Compared to non-Hispanic White adults, childhood health and adversity were not associated with accelerated biological aging for non-Hispanic Black and Hispanic adults, and among these groups, higher midlife SES did not decelerate biological aging. The association between accelerated biological age and health outcomes varied by race/ethnicity; accelerated biological age was less predictive among non-Hispanic Black and Hispanic adults. Among Hispanic adults, foreign-born status was a significant moderator: increased biological age was more strongly linked to morbidity among foreign-born individuals. Conclusions The processes linking life-course conditions to biological aging, and biological aging to later-life health, do not translate uniformly across racial/ethnic groups. Future research should explore the sources of heterogeneity in life-course exposures and the mechanisms by which biological age translates into health outcomes.